2018
DOI: 10.1093/abbs/gmy099
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LGALS12 inhibits porcine adipocyte adipogenesis via PKA–Erk1/2 signaling pathway

Abstract: Increasing intramuscular (IM) fat while concomitantly decreasing subcutaneous (SC) fat content is one major goal of pig breeding. Identifying genes involved in lipid metabolism is critical for this goal. Galectin-12 (LGALS12) has been proven to be an important regulator of fat deposition in mouse models; however, the effect and regulatory mechanisms of LGALS12 on porcine adipogenesis are still unknown. In this study, the effects of LGALS12 on fat deposition were explored with primary culture of porcine SC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In an earlier study, we demonstrated that a knockdown of LGALS12 could decrease the triglyceride (TG) content and alter the expression of FAS , HSL and ATGL in both IM and SC adipocytes [14]. In inhibitor experiments, the decrease of the TG content (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study, we demonstrated that a knockdown of LGALS12 could decrease the triglyceride (TG) content and alter the expression of FAS , HSL and ATGL in both IM and SC adipocytes [14]. In inhibitor experiments, the decrease of the TG content (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ablation of this protein in mice leads to increased lipolysis, decreased adiposity, and amelioration of insulin resistance associated with weight gain [10]. Our previous study with porcine adipocytes showed that the knockdown of LGALS12 decreased adipogenesis, which indicates that it has potential value in pig breeding [14]. However, the regulatory mechanisms of LGALS12 in porcine adipocytes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The similar galectin-12-associated signaling pathways were proposed for differentiation of human sebocytes considering that both the sebaceous gland tissue and sebaceous gland SZ95 cells express same lipogenic factors (C/EBPα, SREBP-1, SCD, and resistin) as adipocytes [ 187 ]. The siRNA knockdown of galectin-12 was also reported to inhibit adipogenesis of porcine adipocytes by downregulating lipogenic genes ( PPARγ and aP2 ) and activating lipid hydrolysis (triglyceride lipase and hormone-sensitive lipase) through the PKA-Erk1/2 signaling pathway [ 188 ]. Lastly, a positive association between cell differentiation (enterocyte lineage) and de novo galectin-12 expression was reported in eight human colorectal carcinoma cell lines (HCT15, KM12, LS180, TC7, CX1, HT-29, SW480, and SW707), which were treated with sodium butyrate [ 189 ].…”
Section: Galectin-12mentioning
confidence: 99%
“…In addition, the lipids-lowering effect of CUR has been also proved in obese mice [ 26 ]. In a diabetic rat model, CUR reduces the contents of triglycerides, total cholesterol, blood glucose and free fatty acids [ 27 ]. These related in vivo investigations indirectly and strongly support our results.…”
Section: Discussionmentioning
confidence: 99%